Synthesis of functionalized 2, 5-dihydropyrrole derivatives via a convenient [3 + 2] annulation of azomethine ylides with allenoates. Issue 36 (4th September 2018) - Huang, Zhusheng; Dai, Zonghao; Zhu, Jin; Yang, Fulai; Zhou, Qingfa
Abstract : A convenient [3 + 2] annulation of azomethine ylides with allenoates to synthesize highly functionalized 2, 5-dihydropyrrole derivatives was developed. Abstract : A convenient [3 + 2] annulation of azomethine ylides with allenoates promoted by triethylamine produced highly functionalized 2, 5-dihydropyrrole derivatives in moderate to excellent yields under mild conditions. The potential utility of this reaction indicates that this reaction could be performed on the gram scale and the synthesized functionalized 2, 5-dihydropyrrole derivatives could be further transformed into other interesting heterocycles. The mechanism for the transformation is a tandem β-addition/Mannich cyclization process.